The Relationship Between Built Environment and Mental Health of Older Adults: Mediating Effects of Perceptions of Community Cohesion and Community Safety and the Moderating Effect of Income - Zhang, Rongrong; He, Xiong; Liu, Ying; Li, Ming; Zhou, Chunshan (Frontiers in Public Health, 2022)
Although a large amount of research has revealed the significant correlation between low-density built environment and the mental health of elderly people in developed countries, it was not until recently that scholars and decision-makers began to pay close attention to the effect of this relationship in high-density built environment and in developing countries. Using point of interest (POI) data from Baidu and data on 20 communities in Guangzhou, China, that were collected through a questionnaire survey, this research aims to examine the relationship between built environment and the mental health of the elderly as well as the physiological-psychological mediating paths between the two, so as to enrich the research on population aging in the high-density urban context in developing countries. The research findings indicate that facility accessibility and distance to parks are significantly positively correlated with the mental health of the elderly and that the number of public transit stations and the distance to these stations are significantly negatively correlated with the mental health of elderly people. Second, the perceptions of community cohesion and community safety have a significant mediating effect between built environment and the mental health of elderly people. Furthermore, the moderating effect analysis results verify the moderating effect of income: with an increase in income, the perception of community cohesion enhances the protection of the mental health of elderly people and reduces the mediating effect of the perception of community safety. The research results enrich studies on the health of elderly people in the high-density urban context in developing countries and provide an important reference for policy-makers and urban planners in their effort to plan and build health-supporting communities and a healthy aging society.